2021
DOI: 10.1109/access.2021.3055374
|View full text |Cite
|
Sign up to set email alerts
|

FPGA Realizations of Chaotic Epidemic and Disease Models Including Covid-19

Abstract: The spread of epidemics and diseases is known to exhibit chaotic dynamics; a fact confirmed by many developed mathematical models. However, to the best of our knowledge, no attempt to realize any of these chaotic models in analog or digital electronic form has been reported in the literature. In this work, we report on the efficient FPGA implementations of three different virus spreading models and one disease progress model. In particular, the Ebola, Influenza, and COVID-19 virus spreading models in addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The unpredictable nature of the pandemic spread has been tackled, on the one hand from the perspective of deterministic chaos [14] , [15] , [16] and, on the other hand, using stochastic models [17] , [18] . Dynamic stochastic models for COVID-19 spread prediction can be broadly categorized into: (i) stochastic differential equations based in classical SIR models [8] , [17] , and (ii) compartmental models combined with Mote Carlo methods [6] , [19] , [20] , [21] .…”
Section: Introductionmentioning
confidence: 99%
“…The unpredictable nature of the pandemic spread has been tackled, on the one hand from the perspective of deterministic chaos [14] , [15] , [16] and, on the other hand, using stochastic models [17] , [18] . Dynamic stochastic models for COVID-19 spread prediction can be broadly categorized into: (i) stochastic differential equations based in classical SIR models [8] , [17] , and (ii) compartmental models combined with Mote Carlo methods [6] , [19] , [20] , [21] .…”
Section: Introductionmentioning
confidence: 99%
“…There are many models introduced for pandemic disease, but in 2021, a covid model 24 was introduced by considering data taken from highly infected countries such as Italy, Japan, South Korea and China has got much importance. The considered model taken from 11 , 24 is given as : where , , shows the daily numbers of new cases, daily additional severe cases and new death cases, respectively. Mathematically, system ( 1 ) exhibits chaotic behavior for initial conditions (184, 30, 8) and parameter values given in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The degree of chaos and unpredictability in a system is determined by its sensitivity to the initial conditions, the bifurcation parameter, and the dense oscillatory solutions. The aforementioned features of chaos in continuous systems are increasing its appeal by using it as a transmitter in secure communication 1 , path planing problems 2 4 , cryptography 5 and motion control 6 but apart from these applications in engineering, the term ”chaos” continues to be associated with negative impact in biological models and still remain as a villain such as Cancer 7 , Ebola 8 , 9 , Influenza 10 , 11 , HIV 12 , 13 and Parkinson 14 epidemic diseases models.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the research on covid-19 is not restricted to biology, but a lot of work can be found in other fields as well, such as, Machine learning [ 6 , 7 ], dynamical systems [ 8 , 9 ]. The covid-19 model [ 10 , 11 ] that we have considered is where , and shows the daily numbers of new cases, daily additional severe cases and new death cases reported per day due to covid, respectively. Mathematically, system ( 2 ) exhibits chaotic behaviour for initial conditions =(184, 30, 8) and parameter values given in Table 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the research on covid-19 is not restricted to biology, but a lot of work can be found in other fields as well, such as, Machine learning [6,7], dynamical systems [8,9]. The covid-19 model [10,11] that we have considered is…”
Section: Introductionmentioning
confidence: 99%